2011
DOI: 10.1111/j.1600-0625.2011.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

A close relationship between type 1 diabetes and vitamin A-deficiency and matrix metalloproteinase and hyaluronidase activities in skin tissues

Abstract: Numerous wrinkles are observed in the skin of streptozotocin (STZ)-induced type 1 diabetic rats, which are similar to those seen in vitamin A-deficient (VAD) rats. Retinoic acid (RA), the active form of vitamin A, promotes the production of collagen in dermis and induces cell growth and inhibition of epidermal differentiation in skin tissues. Normal skin function is maintained by the extracellular matrix (ECM)-degrading enzymes, matrix metalloproteinase (MMP) and hyaluronidase (HAase). This study is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These modifications cannot be explained by the augmented collagen glycation but rather by enzymatic degradation of matrix collagen. Interestingly, further reports have been made regarding higher matrix metalloproteinase (MMP) activities, mainly MMP-2, MMP-8, MMP-9, MMP-13 and MMP-14, in connective tissues, other than bone, in type 1 diabetes [38][39][40][41][42]. To the best of our knowledge, MMP activities have never been assessed in bone tissue of diabetic animals.…”
Section: Discussionmentioning
confidence: 94%
“…These modifications cannot be explained by the augmented collagen glycation but rather by enzymatic degradation of matrix collagen. Interestingly, further reports have been made regarding higher matrix metalloproteinase (MMP) activities, mainly MMP-2, MMP-8, MMP-9, MMP-13 and MMP-14, in connective tissues, other than bone, in type 1 diabetes [38][39][40][41][42]. To the best of our knowledge, MMP activities have never been assessed in bone tissue of diabetic animals.…”
Section: Discussionmentioning
confidence: 94%
“…Liver, pulmonary and renal fibrosis are common pathological states which represent a major global health problem, and effective therapeutic measures are presently unavailable [ 189 ]. The similarities in the ECM modifications occurring in VAD and in some other diseases, and the reversibility of most VAD-induced alterations by RA, suggest that some degree of VAD might be present in those diseases and underscores the potentially beneficial effects of retinoid treatment [ 109 , 138 , 141 , 168 , 190 , 191 , 192 , 193 , 194 , 195 ]. In fact, RA treatment has proved beneficial in several experimental diseases.…”
Section: Discussionmentioning
confidence: 99%
“…RA inhibits the expression of TSP [4], TGF-β1 [54], collagen I [5458], collagen II [59], collagen III [54,58], collagen VII [58], collagen X [59], LN [55,60], α-SMA [55], FN [4,55,56,58,61,62], 5-lipoxygenase (5-LOX) [54], CTGF [54], cysteine-rich protein 61 (CCN1) [63,64], procollagen I [6365], MMP-1 [63,64,66], MMP-2 [67], and is able to down-regulate the accumulation of ECM. However, several independent studies found that RA could up-regulate the expression of FN [57,59], collagen I [59,60], collagen IV [68,69], TSP [57], LN [57,70], MMP-2 [71], MMP-9 [71], GPRC5B [72], integrin α5 [73], IGF1 [74] and IGF2 [74], which results in the opposite effect as reported above, i.e ., the induction of ECM accumulation [68,75,76].…”
Section: Signaling Pathways Of Role Of Ra In the Ecm Metabolismmentioning
confidence: 99%